In Comparison to PSA, Interim Ga-68-PSMA PET/CT Response Evaluation Based on Modified RECIST 1.1 After 2nd Cycle Is Better Predictor of Overall Survival of Prostate Cancer Patients Treated With 177Lu-PSMA - Prasad, Vikas; Huang, Kai; Prasad, Sonal; Makowski, Marcus R.; Czech, Norbert; Brenner, Winfried (Frontiers in Oncology, 2021)
Background: Prostate-specific membrane antigen (PSMA) targeting radioligands have transformed treatment of prostate cancer. Radioligand therapy (RLT) with 177Lu-PSMA in metastasized castration resistant prostate cancer (mCRPC) achieves objective response and disease stabilization in roughly two third of patients, whereas one third of patients progress. This study was performed to assess the role of interim PSMA PET/CT after the 2nd cycle of RLT for early prediction of overall survival in patients undergoing RLT with 177Lu-PSMA. Methods: 38 mCRPC patients (68.9±8.1 y) treated with at least 2 cycles of RLT at 8 week intervals and interim 68Ga-PSMA PET/CT (PET) at 8-10 weeks after the 2nd cycle of RLT were included in this study. Prostate-specific antigen (PSA) response was evaluated according to Prostate Cancer Working Group 3 criteria. Radiographic response assessment of soft tissue, lymph node and bone lesions were performed according to RECIST 1.1 including the PET component. Patients’ data were collected for follow-up from the local Comprehensive Cancer Center Register. Results: Median follow-up was 19.7 months (4.7-45.3). PSA response after the 2nd therapy cycle showed partial remission (PR) in 23.7%, stable disease (SD) in 50% and progressive disease (PD) in 26.3% of patients. In comparison, 52.6%, 23.7% and 23.7 % of patients showed PR, SD and PD respectively on PET/CT. The strength of agreement between PSA response and PET/CT response criteria was only fair (kappa 0.346). Median overall survival (OS) was 22.5 months (95% CI: 15.8-29.2). Median OS stratified to PSA / PET response was 25.6 / 25.6 months for PR, 21.7 / 30.6 months for SD and 19.4 / 13.1 months for PD (p=0.496 for PSA and 0.013 for PET/CT response). Conclusions: Interim PSMA PET/CT based response evaluation at 8-10 weeks after the 2nd cycle of RLT is predictive of overall survival and PD in patients treated with 177Lu--PSMA. In contrary, PSA appears to have only limited predictive value.